Dampak Pembentukan Tiga Provinsi Baru Terhadap Kinerja Perekonomian Papua - Winardi (Ministry of Home Affairs, 2023)
Currently, there have been three new autonomous regions established as a result of regional expansion in Papua Island, namely South Papua Province, Central Papua Province, and Papua Mountain Province. The formation of new provinces is expected to become a prime mover for accelerating equitable economic development in the Papua region. Therefore, it is necessary to conduct a study to analyze the impact of the formation of the province on the economic performance of Papua Island. The method used is the Final Demand Impact analysis of the Input-Output (I-O) Table. The results of this study indicate that the formation of the province has an impact on increasing the economic output of Papua Island by 37.7 percent and 69.5 percent for an increase in added value and contributing to an increase in employment of 71.1 percent or as many as 1.5 million people. The improvement in the economic performance of Papua Island, in turn, will indirectly have a positive effect on improving people's welfare and strengthening regional competitiveness and the contribution of the regional economy to the national economy. In addition, it also reduces the level of inequality in economic development nationally, which is still dominated by Java Island.